2023
DOI: 10.3390/horticulturae9060658
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pollen-Collecting Abilities between Apis mellifera L. and Bombus terrestris L. in the Oil Tree Peony Field

Abstract: The lack of pollinators in the oil tree peony field was a serious problem for the seed yield. In the preliminary studies, we found that the seed rate of oil tree peonies was significantly improved by supplementing bees during the flowering stages in the pollination net room. In addition, the performance of Apis mellifera L. was better than Bombus terrestris L. To understand the interaction relationship between flowering characteristics and the managed bees, and the pollen-collecting ability of different specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Insect pollination has been found to significantly enhance both the rate and quality of fruit development, as evidenced by similar findings in P. ostii 'Feng Dan' cultivation [18]. Furthermore, investigations on the impact of different bee species on seed yield have revealed that honey bees exhibit superior pollination efficiency compared to bumble bees [19,20]. However, the tree peony lacks nectarines, and the cost of building sealed greenhouses and buying insects may far outweigh the benefits of increased yields, so it is necessary to explore new and feasible pollination methods.…”
Section: Introductionmentioning
confidence: 64%
“…Insect pollination has been found to significantly enhance both the rate and quality of fruit development, as evidenced by similar findings in P. ostii 'Feng Dan' cultivation [18]. Furthermore, investigations on the impact of different bee species on seed yield have revealed that honey bees exhibit superior pollination efficiency compared to bumble bees [19,20]. However, the tree peony lacks nectarines, and the cost of building sealed greenhouses and buying insects may far outweigh the benefits of increased yields, so it is necessary to explore new and feasible pollination methods.…”
Section: Introductionmentioning
confidence: 64%